Propuesta de mejora para la cadena de abastecimientos en relación con el producto Brote de Soya de la empresa NICCA (2022)
The general purpose of this work was to develop an improvement proposal for the supply chain in relation to the Soybean Sprout product in order to reduce the logistics costs of the company. A critical degree analysis method was used, which s NICCA eeks to collect information in order to identify the current state of the supply chain. In addition, from the different analyzes the improvement actions are prioritized to give continuity to the improvement proposals, then the most feasible and effective i mprovement options are selected. Each proposal will be adapted to the objectives to be achieved within the company